Application of 3D Printing Based on the Brain MRI Dicom Dataset as a Learning Media for MRI Anatomy for Radiology Students - Alifia Dian Rizqi Arshyva; Fatimah Fatimah; Darmini Darmini (International Journal of Health and Social Behavior, 2026)
Background The brain is a complex organ and quite difficult to study, so effective learning methods are needed to improve understanding of brain anatomy. 3D printing technology has been widely used in the medical world.medicine, especially as a learning medium for anatomy for medical students, but currently there are no radiology educational institutions that provide 3D learning aids printing which are converted directly from DICOM MRI image results.Research Purposes : To prove the difference in application between 3D printing and 2D DICOM MRI brain datasets in learning brain anatomy in radiology students. Method, The research was conducted using a design true experiment with a sample of 76 students divided into experimental and control groups. The experimental group used 3D printing media, while the control group used 2D DICOM images.Results, The average score of the experimental group was higher (88.76) than the control group (56.21). Statistical tests showed a significant difference between the two groups (p < 0.05). Conclusion, Learning brain anatomy using 3D printing media is more effective than the 2D DICOM image learning method (N-Gain 0.776).